PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS METODE STRUKTURAL ANALITIK SINTETIK (SAS) UNTUK PEMBELAJARAN MEMBACA PERMULAAN - Iswara, Prana Dwija; Djuanda, Dadan; dwi pusparini, Inayah Septyani Dwi (Cerdas Proklamator, 2024)
Reading is very important for students to have reading skills, if they have good reading skills, it will be very easy for them to master the material they are learning. This research aims to develop digital teaching materials based on the Structural Analytic Synthetic (SAS) method to help students in carrying out the initial reading learning process. The research method used is research and development (R&D) using the ADDIE model (analysis, design, development, implementation, evaluation) adaptation of Dick and Carey. The data processing in this study uses qualitative and quantitative techniques using observation, interview, and validation techniques from experts. The results of the assessment of teaching materials based on the SAS method developed show that the validation score of material experts obtained a score of 97% and media experts 87% with a category that is very valid and suitable for use. The results of interviews and observations on the trial of this digital teaching material show that in terms of appearance, the color of the game throughout the material really attracts the attention of students so that it makes students very enthusiastic and interested in learning to read first. With this, it can be concluded that the use of digital teaching materials based on the SAS method can help students in learning to learn to read initially.